Geological Survey of Canada response to the Summary Report of the Review Committee on GSC'S Minerals Geoscience Program - Duke, Murray (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2000)
Summary The Geological Survey of Canada accepts most of the Canadian Geoscience Council Review Committees recommendations and is already acting on some of them. Integration of mapping and metallogenic activities should be facilitated by the new Project Approval System, which will help achieve the cultural change called for by the Committee. We agree that there is aneed to recruit new young scientists, and that digital data bases need to be made available, and we are active in both areas. Increased funding for minerals research is being sought; some new funds have been attained for the 2000-2003 period. The GSC is grateful for the useful insights and recommendations provided by the Review Committee.